Singlet oxygen production by photosystem II is caused by misses of the oxygen evolving complex - Mattila Heta; Mishra Sujata; Tyystjärvi Taina; Tyystjärvi Esa (WILEY, 2022)
Singlet oxygen (O-1(2)) is a harmful species that functions also as a signaling molecule. In chloroplasts, O-1(2) is produced via charge recombination reactions in photosystem II, but which recombination pathway(s) produce triplet Chl and O-1(2) remains open. Furthermore, the role of O-1(2) in photoinhibition is not clear. We compared temperature dependences of O-1(2) production, photoinhibition, and recombination pathways. O-1(2) production by pumpkin thylakoids increased from -2 to +35 degrees C, ruling out recombination of the primary charge pair as a main contributor. S(2)Q(A)(-) or S(2)Q(B)(-) recombination pathways, in turn, had too steep temperature dependences. Instead, the temperature dependence of O-1(2) production matched that of misses (failures of the oxygen (O-2) evolving complex to advance an S-state). Photoinhibition in vitro and in vivo (also in Synechocystis), and in the presence or absence of O-2, had the same temperature dependence, but ultraviolet (UV)-radiation-caused photoinhibition showed a weaker temperature response. We suggest that the miss-associated recombination of P(680)(+)Q(A)(-) is the main producer of O-1(2). Our results indicate three parallel photoinhibition mechanisms. The manganese mechanism dominates in UV radiation but also functions in white light. Mechanisms that depend on light absorption by Chls, having O-1(2) or long-lived P-680(+) as damaging agents, dominate in red light.